Integrating Role Play in Islamic Education for Character Value and Cognitive Achievement in Preschool Learners - Irlina, Andi; huda, nuril; hermina, dina; Ahmad, Ahmad (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
This research investigates the integration of role play in teaching Hadith to strengthen the character development of preschool learners. The study examines how role-playing activities can enhance the understanding of Islamic principles and the application of Hadith in real-life situations among preschool learners. Employing a quantitative experimental design, the study assesses the impact of incorporating role play into Islamic Studies on the character development of preschool learners at Paud IT Al Mansyur in Kotabaru Regency, South Kalimantan. The experiment involved two groups of preschool learners, each consisting of 10 participants. The experimental group engaged in role-playing scenarios designed to teach Hadith and key Islamic values such as self-esteem, empathy, honesty, love, affection, and social responsibility. The control group followed traditional teaching methods. Pre- and post-intervention assessments measured improvements in character traits. The results indicated that the experimental group showed significant improvement in character development compared to the control group. These findings suggest that integrating role play into Islamic Studies, particularly in teaching Hadith to preschoolers, is an effective pedagogical strategy for fostering holistic development, blending moral education with cognitive achievement in a synergistic manner.